Diagnosing a Paper Dryer Malfunction in PT.Bamindo Agrapersada Using the Method DecisionTree - Jurdan Ariga (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
PT. BAMINDO AGRAPERSADA is a private company that processes bamboo into paper and sells it to consumers. In an industrial field, problems often occur to overcome damage to paper drying machines because mechanics are difficult to find and sometimes time is not possible so that operations are hampered while production targets must be completed immediately. Decision Tree which is a tree that is used as a reasoning procedure to get answers to the problems entered. Decision trees provide a way to present algorithms with conditional control statements that include branches in decision-making steps that lead to a favorable outcome. With the Decission Tree, it can minimize damage to the paper drying machine and help solve problems in the PT. BAMINDO AGRAPERSADA industry.